Digitalizing of Fiqh Teaching Materials Based on Contextual Teaching and Learning - Fauzil Adzim (Edukasia Islamika, 2022)
This article aims to: (1) develop digital-based teaching materials with a Contextual Teaching and Learning approach; (2) testing the effectiveness of using digital teaching materials for fiqh subjects with a Contextual Teaching and Learning approach to improve the learning outcomes of class VII students at SMP Diponegoro Depok, Sleman Regency. This article uses an R&D research design with the ADDIE model. Data collection techniques in the form of interviews, questionnaires, tests and observations. Data analysis by t-test (one-group pretest-posttest) and N-gain. Results The development of flipbook teaching materials for Jurisprudence subjects based on Contextual Teaching and Learning (CTL) focused on taharah material for class VII packaged in digital form using the Kvisoft Flipbook Maker application. Flipbook teaching materials are equipped with features, namely being able to read the yellow book (Arabic Pegon), technological skills, HOTS-based questions, QR Code-based links for deepening material, habituation, exemplary stories, mind mapping and summaries. Flipbook teaching materials for Jurisprudence subjects based on Contextual Teaching and Learning (CTL) have been able to improve student learning outcomes on the Thaharah material. The results of the N-Gain calculation obtained from the comparison of the average pretest and posttest values ​​of 0.59 or 59% are in the category of quite effective for improving student learning outcomes in Fiqh learning.